Damaged Speleothems and Collapsed Karst Chambers Indicate Paleoseismicity of the NE Bohemian Massif (Niedźwiedzia Cave, Poland). Issue 3 (12th March 2021) - Szczygieł, Jacek; Sobczyk, Artur; Hercman, Helena; Mendecki, Maciej J.; Gąsiorowski, Michał
Abstract: Multiphase speleothem damage and passage collapse in Niedźwiedzia Cave (NE Bohemian Massif, Poland) were dated with U‐series methods, revealing five events: (1) 320–306 ka, (2) 253–236 ka, (3) 162–158 ka, (4) 132–135 ka, and (5) >21 ka. Events 1, 3 and 4 are robustly constrained, and events 2 and 5 are less certain. Although we cannot unambiguously exclude other agents (frost or gravity collapses), the most likely trigger of damage in the cave was an earthquake, which is supported by timing (the damage occurred independently from climatic conditions in cold and warm periods) and deformation style (damage to the ceiling and walls as well as the passage floor). We applied ground motion models to determine the probable seismic source size, which is most likely the Sudetic Marginal Fault ‐ one of the most pronounced tectonic structures in Central Europe. Located <20 km from the cave and with documented earthquakes of M > 6, the Sudetic Marginal Fault can produce peak ground acceleration values high enough to break speleothems. The other plausible seismic sources are faults in the Upper Nysa Kłodzka Graben located to the east and the Trzebieszowice‐Biela Fault. Although there are sparse historical data that would allow estimating linked seismic hazards, the <8 km distance between the cave and faults should suffice to destroy the speleothems. Niedźwiedzia Cave shielded environmental earthquake effects from erosion. This study shows the advantage of employing speleoseismology in moderate seismic regions, where earthquake effects are rarely preserved in the geological record. Key Points: In low to moderate seismic regions, where earthquake effects are rarely preserved in the geological record, caves can shield them from erosion Speleoseismological research in Niedźwiedzia Cave revealed five events of cave damage between 320 and 21 ka Based on ground motion models, the probable seismic source of damage within the cave is the Sudetic Marginal Fault